81.2k views
24 votes
Check the solution.

y=x-7
y=-4+3

solution: (2,-5)

check in first eq:



check in 2nd eq:​

User Te
by
4.4k points

1 Answer

5 votes

Answer:

Both equations, when we replace the solution, generate identities.

Explanation:

We are given the following system:

y = x - 7

y = -4x + 3

We are given the following solution.

(2,-5).

First equation:

We have to show that when x = 2, y = -5. So

y = x - 7

-5 = 2 - 7

-5 = -5

So ok

Second equation

We have to show that when x = 2, y = -5. So

y = -4x + 3

-5 = -4(2) + 3

-5 = -8 + 3

-5 = -5

We generate both identities, so the solution is checked.

User NCrazed
by
4.1k points